The liminal music studio: between the geographical and the virtual. - Order, Simon (Critical Arts: A South-North Journal of Cultural & Media Studies, 2016)
The dramatic anthropological shifts in music production practices in the post-analogue world have been primarily driven by the ever-increasing functionality of digital audio technologies. Technologies are pertinent actors in the music production process, more than ever before. A new trend in music production is a move towards the mobile tablet computer as a production tool. This article emerged from my own practice-led research into music production on a tablet computer whilst travelling, and at international destinations. Using evocative autoethnography, I diarised my mobile music production, concluding that mobility positively impacted creativity. Reflection led me to ask: What factors are at play and could a theorisation of mobile production practice be articulated? Mobility is more than transplanting music production to another place. Rather, mobility asks us to reconsider fundamental notions central to musical practice. Space and environment become cognitive stimuli, echoing the seminal work by Mel Rhodes on creativity. Rhodes popularised the term ‘press’ to describe the multi-factorial impact of experience on human creativity. This study theorises a multi-sensorial approach where human mobility and connection with place enhance musical creativity. Second, music data mobility amplifies production options. The connected mobile musician can absorb the perceptual richness of physical travel and also the stimuli of the electronic ether. Where is creativity? This article proposes that creativity for the mobile musician is experienced in a liminal space between the geographical and the virtual.